Parameter analysis of copper-nickel-tungsten prepared via powder metallurgy process for electrical discharge machining of polycrystalline diamond - Sabri, Ainaa Mardhiah (2019)
Polycrystalline Diamond (PCD) tools have an outstanding wear resistance. The electric conductivity of PCD caused by the conductive binding material (Cobalt) makes it possible to machine PCD tools with EDM. Electrode used in EDM of PCD must have better porosity, electrical and thermal conductivity. Therefore, this research presents the works in production of Cu-Ni-W electrode by powder metallurgy route. Production of powder metallurgy parts involve mixing of the powder with additives or lubricants, compacting the mixture and heating the green compacts in an Argon gas furnace so the particle bond to each other. Two levels of full factorial with six centre points and two replication technique was used to study the influence of main and interaction effects of the powder metallurgy parameter. There were four factors involved in this experiment. Factor A which is Type of Cu-Ni; Type A and Type B was defined as categorical factor. Factor B in which Composition of W; 5 Wt.%, 15 Wt. % and 25 Wt.%, was defined as numerical factor. Factor C which is the Compaction load; 7, 8 and 9 tonne and Factor D which is Sintering temperature; 635 ℃, 685 ℃ and 735 ℃ were also defined as numerical factor. Optical Microscope, Scanning Electron Microscopy (SEM) and Energy Dispersive X-ray (EDX) was used to analysed the microstructure and surface morphology of Cu-Ni-W electrode. The best parameter combination to produced better porosity, electrical and thermal conductivity for both Type A and Type B was 5 Wt.% of W, compaction load at 9 tonne and sintering temperature at 735℃. The best response for Type A is 12.65% of porosity, 14.40 IACS% of electrical conductivity and 413.26 W/m.℃ of thermal conductivity. While that, the best response for Type B were 9.36% of porosity, 16.66 IACS% of electrical conductivity and 345.21W/m.℃ of thermal conductivity. From the calculation of Maxwell’s Equation, Type A and Type B had the highest electrical conductivity of 58.48 IACS% and 77.35 IACS% respectively at W content of 5Wt.%. Type A and Type B also had the highest thermal conductivity of 369.86 W/m.℃ and 310.24 W/m.℃ respectively at W content of 5 Wt.%. Besides that, thermal conductivity also increased with the temperature increased until 450℃.